Concrete Pavement Layers Investigation with GPR in the BR-101 Highway - Cunha, Matheus Rodrigues; Borges, Welitom Rodrigues; Cunha, Luciano Soares da (Anuário do Instituto de Geociências, 2019)
In the construction project of a highway, some rules related to the materials and thicknesses of the layers must be followed to guarantee that the project is carried out properly. From denunciations accusing irregularities on the project of the highway BR-101, on Northeastern Brazil, we applied the Ground Penetrating Radar (GPR) method to investigate the depths of the base and subbase layers. It was used a 900 MHz shielded antenna, acquiring 45 km of data. The medium velocity was obtained indirectly through a hyperbolic fit and calibrated comparing it with the depth of a test trench. The results pointed out depth variations for both of the layers along the analyzed track, however the average depth only deviates from the original project for the base layer.